2016
DOI: 10.18805/ijar.v0i0f.3797
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of native chicken populations reared underfamily-based free-range scavenging system in Odisha, India

Abstract: The genetic architecture of 10 rural poultry populations in two distant tribal districts of Mayurbhanj and Kalahandi of Odisha state in India were studied for 15 quantitative and 11 qualitative characteristics through a field survey. Analysis of dispersion was conducted to test the simultaneous significance of mean differences in above characteristics and was found to be highly significant (p is less than 0.01). Cluster-I (Khairi and Kabri), cluster-II (Hansli, Gujuri, Dumasil, Dhabla, Kalua and Khadia), clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(Yaemkong, 2014;Kavin et al, 2016) Faruque et al, 2010Abinawanto et al, (2017) also reported that the body weight, shank length, and wing length of the native chicken were 1.67 kg, 11.26 cm, and 23.21 cm, respectively. Biodiversity Singh et al (2016) reported in their study that the characteristic of Thai native chicken was higher and slimmer than the broiler and adult male native chicken was 3.0-3.5 kg of average body weight. Studied chickens with 13.99 months, andYaemkong, (2014); Yaemkong and Tuan,(2016).…”
Section: Discussionmentioning
confidence: 92%
“…(Yaemkong, 2014;Kavin et al, 2016) Faruque et al, 2010Abinawanto et al, (2017) also reported that the body weight, shank length, and wing length of the native chicken were 1.67 kg, 11.26 cm, and 23.21 cm, respectively. Biodiversity Singh et al (2016) reported in their study that the characteristic of Thai native chicken was higher and slimmer than the broiler and adult male native chicken was 3.0-3.5 kg of average body weight. Studied chickens with 13.99 months, andYaemkong, (2014); Yaemkong and Tuan,(2016).…”
Section: Discussionmentioning
confidence: 92%
“…Northern Odisha are the major sources of biodiversity in poultry. Apart from crop production, native poultry rearing by tribal people in such tribal districts has become a chief source of their livelihood (Singh,et. al.…”
Section: Mayurbhanj and Keonjhar Districts Inmentioning
confidence: 99%